Long-term follow-up after fetal radiation exposure during endoscopic retrograde cholangiopancreatography - Laudanno, Oscar; Garrido, Jose; Ahumarán, Gabrial; Gollo, Pablo; Khoury, Marina (Endoscopy International Open, 2020)
Background and study aims The main concern about endoscopic retrograde cholangiopancreatography (ERCP) during pregnancy is the risk of radiation exposure to the fetus. The potential exists not only in the short-term, but also in the long-term and includes growth and development problems and the possibility of childhood cancer. Little is known about the long-term effects of fetal radiation exposure at the time of ERCP. The aim of the study was to report the long-term outcome of babies born after radiation exposure to mothers who underwent ERCP during pregnancy. Patients and methods This was a single-center retrospective cohort study. We included 24 consecutive pregnant patients who underwent ERCP due to choledocholithiasis and their children, between June 1997 and June 2015. All patients and their babies were followed up until birth to assess their short-term outcome. To assess long-term outcomes, from September 2014 to September 2015, a comprehensive medical interview was conducted with the mothers and their children. We also evaluated medical records, lab tests, school report cards, and the families completed a questionnaire inquiring about perceived health status of the children. Results Fifteen patients had full-term pregnancies. One patient had a preterm delivery (32 weeks) due to preeclampsia. There were no cases of miscarriage, stillbirth or fetal malformations. Long-term follow-up was performed at a mean age of 11.08 years (range 1–18) for the children, with no developmental delays, poor school performance, or malignancies found. Conclusions Long-term outcome in children born after radiation exposure during ERCP was unremarkable.